2017
DOI: 10.1007/s12031-017-0905-1
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 4 Forms a Macromolecular Complex with Glutamate Transporter 1 and Mu Opioid Receptor in Astrocytes and Participates in Morphine Dependence

Abstract: The water channel aquaporin 4 (AQP4) is abundantly expressed in astrocytes and provides a mechanism by which water permeability of the plasma membrane can be regulated. Evidence suggests that AQP4 is associated with glutamate transporter-1 (GLT-1) for glutamate clearance and contributes to morphine dependence. Previous studies show that AQP4 deficiency changed the mu opioid receptor expression and opioid receptors' characteristics as well. In this study, we focused on whether AQP4 could form macromolecular com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…In addition to cystine-glutamate exchange, other mechanisms of glutamate release by astrocytes have been reported (119), but none have yet been found to contribute to glutamate plasticity observed after extinction from opioids or during reinstated seeking. For instance, whereas stimulating astroglial MORs increases glutamate transmission in hippocampus via the glutamate channel TREK-1 (120), this channel is also downregulated after long-term opioid use (121).…”
Section: Glutamate Transport and Releasementioning
confidence: 99%
“…In addition to cystine-glutamate exchange, other mechanisms of glutamate release by astrocytes have been reported (119), but none have yet been found to contribute to glutamate plasticity observed after extinction from opioids or during reinstated seeking. For instance, whereas stimulating astroglial MORs increases glutamate transmission in hippocampus via the glutamate channel TREK-1 (120), this channel is also downregulated after long-term opioid use (121).…”
Section: Glutamate Transport and Releasementioning
confidence: 99%
“…As a result, it can be concluded that, regardless of the role of astrocyte in synapse, the pathologic LTP cannot be controlled. Some researchers believe that astrocyte dysfunction can lead to addiction [ 28 , 30 ]. Thus, it can be concluded that without the manipulation of astrocyte function, we may not be able to inhibit the pathological LTP induction.…”
Section: Discussionmentioning
confidence: 99%
“…Further excitation of pyramidal neurons leads to more glutamate release, which means CA1 pyramidal neurons and astrocytes are going to be more excited than normal level. Furthermore, opioids decrease astrocytic glutamate transporter1 (GLT1) activation which is responsible for the glutamate uptake from the synaptic cleft [ 28 , 30 ]. As a result, reuptake of glutamate is reduced by astrocyte, and therefore more glutamate can be found in the synaptic cleft.…”
Section: Neurobiology Of Opioid Signaling In Synaptic Plasticity and mentioning
confidence: 99%
See 1 more Smart Citation
“…The coassembly between AQP4 and EAAT2 is mediated by a region within amino acids 252–323 of the AQP4 C terminus. Interestingly, morphine was found to regulate expression of the complex via activation of protein kinase C, and it is suggested that the complex might play a role in morphine dependence . In another recent study, the astrocytic Fc receptor was found to be required for autoantibody‐induced internalization of AQP4 and EAAT2, a finding which may aid development of therapies to treat neuromyelitis optica, an autoimmune disease in which AQP4 autoantibodies cause CNS immunopathology and secondary CNS demyelination .…”
Section: Amino Acid Transporter (Slc6a11 and Slc1a2) Interactions Witmentioning
confidence: 99%